DEVELOPMENT OF FLASHCARD MEDIA IN INTRODUCING MEDICINE PLANT BIODIVERSITY - Aviaska Azizah; Fakhri Fakhri; Supardi Uki Sajiman (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2023)
The development of interesting learning media needs to be done because of the very rapid development of technology and coupled with the Covid-19 pandemic which requires the availability of attractive media so that it can help students in learning both face-to-face and virtual. The purpose of this research is to determine the level of success of the flashcard media provided as support for the learning process. The research used the ADDIE development approach. This method leads researcher in producing a product in the form of a flashcard to be tested and measured to assess its feasibility. The trial was conducted on 44 students at SMAN 1 Tangerang Selatan. Affective assessment shows very good criteria with an average of 84. The highest score is shown in a proactive attitude of 90 and the low score is shown in a polite attitude of 80. The process assessment has the lowest score obtained by students in the form of a playing score of 30 while the highest playing score is 75, in the learning process, the lowest score is with two types of assessment, namely the pre-test is 17 and the post-test is 36, the highest pre-test score is 45 while the post-test value is 98. Through the assessment, the percentage score obtained is N-Gain of 0.83. Learning during the Covid-19 pandemic must be accompanied by fun learning so that it is not boring and fosters enthusiasm for learning. Through flashcards students can learn and can become peer tutors for their friends.